2006
DOI: 10.1089/dna.2006.25.684
|View full text |Cite
|
Sign up to set email alerts
|

The Pro-inflammatory Cytokines, IL-1βand TNF-α, Inhibit Intestinal Alkaline Phosphatase Gene Expression

Abstract: High levels of the pro-inflammatory cytokines, interleukin-1beta (IL-1beta) and tumor necrosis factor-alpha (TNF-alpha), are present in the gut mucosa of patients suffering form various diseases, most notably inflammatory bowel diseases (IBD). Since the inflammatory milieu can cause important alterations in epithelial cell function, we examined the cytokine effects on the expression of the enterocyte differentiation marker, intestinal alkaline phosphatase (IAP), a protein that detoxifies bacterial lipopolysacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 77 publications
1
38
0
Order By: Relevance
“…However, there are no reports regarding the ability of exogenous IAP to regulate endogenous IAP expression. A few studies have suggested that herbal extracts and sodium butyrate may play a role in regulating IAP expression (Malo et al, 2006;Levkut et al, 2011). The present investigation demonstrated that EO, NaBu and exogenous IAP all up-regulate intestinal levels of IAP, which can contribute to the maintenance of local intestinal immunity.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, there are no reports regarding the ability of exogenous IAP to regulate endogenous IAP expression. A few studies have suggested that herbal extracts and sodium butyrate may play a role in regulating IAP expression (Malo et al, 2006;Levkut et al, 2011). The present investigation demonstrated that EO, NaBu and exogenous IAP all up-regulate intestinal levels of IAP, which can contribute to the maintenance of local intestinal immunity.…”
Section: Discussionsupporting
confidence: 57%
“…In the present study, the reduction of p65 and increased IAP expression in response to LPS+NaBu treatment suggest that, at least in part, the overexpression of IAP may down-regulate NF-κB signaling. The mechanism of action was reported be through histone hyperacetylation (Malo et al, 2006). Other studies examining the effects of NaBu on intestinal inflammation with regard to other pathways were summarized by Canani et al (2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the fractionated cell components and lysate of all cells used pNPP as the substrate for the AP enzyme. As reported (32), to determine IAP activity, spectrophotometric quantitation of the hydrolyzed product of pNPP, p-nitrophenol, was used and calculated as nmol of pNPP hydrolyzed per minute per microgram of protein. To confirm that the AP activity was only from IAP, samples were also exposed to 10 mM phenylalanine, a known inhibitor of IAP, and 10 mM homoarginine, known to have no effect on IAP activity.…”
Section: Iap Enzyme Activity and Lps-dephosphorylating Assaymentioning
confidence: 99%
“…A growing body of evidence suggests that AP plays an important part in host defense in dephosphorylating extracellular ATP [8,9], a known pro-inflammatory molecule, into adenosine, a key molecule in tissue protection mechanisms [10], while extracellular ATP is also involved in the activity of phosphatases and phosphodiesterases [11]. This ecto-enzyme also plays an important role against inflammatory reactions due to lipopolysaccharide (LPS endotoxin) release during bacterial infection [12,13].…”
Section: Introductionmentioning
confidence: 99%